Kuliah Kerja Nyata (KKN) Di Desa Cibitung Kulon Kecamatan Pamijahan Bogor - Sopian Sopian; Okpatrioka Okpatrioka; Sandi Sandi; Aditia Pebriansyah; Dika Rojaliitia Pebriansyah; Indah Puspita Sari (Universitas Kristen Indonesia Toraja, 2023)
Real work lectures are a form of community service activities by students with cross-scientific and sectoral approaches at certain times and regions. One form of knowledge transfer from student lecturers that is considered lacking in equipping students to work directly into the community, the STKIP Arrahmaniyah campus carries out real work lectures as one of the obligations of the tri dharma of higher education. The results of the Field Work Lecture (KKN) in Cibitung Kulon Village, Pamijahan District, Bogor are: First, the STKIP Arrahmaniyah KKN for the 2023 Academic year was felt to be quite successful and smooth in achieving the goals that had been programmed. Second, the implementation of KKN for one and a half months is felt to be short when it is associated with the density of the programs implemented. Third, with the assistance of the Village Head and all stakeholders and residents of Cibitung Kulom Village, they can carry out all the programs that will be implemented. Fourth, the holding of KKN by STKIP Arrahmaniyah provides many benefits for all.